Semiotika Komersialisasi Islam: Analisis Produk Iklan “Resik V Keluarga Sakinah” di Televisi - Koirudin, Kolik; Habsari, SettingsSri Kusuma; Ardianto, Deny Tri (Jurnal Komunikasi Islam, 2020)
This article aims to analyse the meaning of the construction of Islam in the "Resik V” advertisement of the "Sakinah Family" version on television. There are two research questions raised as a focus of the study, namely the reason why the producer of "Resik V" Ad does "Islamisation" the product? How does "Resik V" Ad put the narratives and codes of Islam on this product? Using Roland Barthes's semiotic analysis, the results of this study found that, first, “Resik V“ advertising was the result of the construction marketing strategy which provided an illusion and adaptation in order to be accepted by Muslim consumers. Second, the narration and co-de of Islam within Ad product was a commodification of religion since the main key for the sakinah family mainly because of faith and obedience to Allah Swt, and not merely maintaining the cleanliness and firmness of the female sex organs.